Estudo Comparativo da Resistência ao Desgaste Abrasivo de Revestimentos Duros dos Tipos FeCrC, FeMn, FeTiCW e FeNbC - Teodoro, Maicon Roberto (2021)
This paper evaluated the resistance to abrasive wear of four types of hard coatings applied by welding to steel used in the sugar and ethanol and mining sectors that can coat defriber hammers, sugarcane chopping knives or loader teeth, in order to increase the service life of the parts and reduce the time of maintenance stops, which optimizes the production system. The coatings evaluated were manganese austenitic (FeMn), FeCrC with high chromium content, FeTiCW containing mixed tungsten-titanium carbide and FeNbC with niobium carbide. The coatings were deposited by the electric arc welding process on a 1020 steel substrate. The characterizations of the coatings were carried out by metallography, energy dispersive spectroscopy (EDS) analysis to identify the chemical elements present in the precipitates formed and Vickers microhardness test. The coatings were submitted to two types of tests to evaluate the abrasive wear resistance of the coatings studied. The fixed ball micro-wear test was performed using 4N, 8N and 12N loads. The rubber wheel test, standardized by ASTM G65:2016, was performed with stops every 10 minutes until completing 30 minutes, and in continuous test of 30 minutes, whose wear resistance was determined volumetric loss by weighing the samples. As a result, the presence of (Fe,Cr)7C3 carbide was observed in the FeTiCW, FeCrC and FeNbC coatings. The hard ternary WTiC carbides formed in the FeTiCW coating adhered and distributed in a martensitic matrix provided the highest hardness among all the coatings studied. The microstructure of the FeNbC coating was characterized by the formation of (Fe,Cr)7C3 carbides adhered to the eutectic matrix (austenite and chromium carbides) with lower hardness than that of the FeCrC coating containing only polygonal (Fe,Cr)7C3 chromium carbides, which are smaller and homogeneously distributed in the eutectic matrix. The FeMn coating showed an austenitic matrix with micropores from the welding process with the lowest hardness among the coatings studied. The results of the fixed ball wear test demonstrated that the 8N load is more severe than the test performed with 12N loads, which due to the large contact load prevents the abrasive from being transported between the sample and the ball. In the rubber wheel wear test, it was observed that the cumulative rate of volumetric loss is maintained with increasing test time, obtaining percentage deviations below 15%. However, the allowable error calculations were below 5%, showing that both tests demonstrate repeatability and reliability above 95%, evidencing that the increase in procedure B time, which is specified in 10 minutes, is ideal, and does not require an increase in test time to evaluate the coatings. In the comparative analysis of the results obtained in the micro wear and rubber wheel test, it was observed that the FeNbC coating was more wear resistant in both tests, followed by the FeCrC coating and FeTiCW coating, with the FeMn coating being the least wear resistant. For the FeMn coating, it was observed that for the fixed ball micro-wear test, increasing the test load provided improvement in wear resistance, evidencing that the mechanical maceration mechanism increases wear resistance as the coating is subjected to the work. It was concluded that higher hardness does not always determine higher wear resistance, since the FeNbC coating with the lowest hardness (569 HV) among the carbide-forming coatings was the most wear resistant, while the FeCrC coating (630 HV) showed higher wear resistance than the FeTiCW coating that has harder WTiC carbides (669 HV), which showed the lowest resistance among the coatings due to the high hardness and brittleness of the carbides, and its wear resistance was higher only than the FeMn coating (261HV).